Multi-Area OSPF Analysis Using Virtual Link and GRE Tunnel - Miftahul Huda; Widyastuti Andriyani (Eduvest - Journal of Universal Studies, 2025)
This study discusses the implementation and analysis of network performance using multi-area OSPF (Open Shortest Path First) with the application of Virtual Link and GRE Tunnel. OSPF is a dynamic routing protocol that is often used in large networks due to its ability to find the shortest path quickly and efficiently. However, on large networks, the use of OSPF in a single area can increase routing overhead and slow down convergence times. Therefore, multi-area OSPF is a solution by limiting the spread of routing information only to related areas. This study uses an experimental method with the PNETLab simulator running five Cisco routers. The test was carried out by measuring QoS parameters such as throughput, packet loss, jitter according to TIPHON standards and OSPF convergence time using iPerf3 and Wireshark software. The results show that multi-area OSPF with Virtual Link has a more stable performance than GRE Tunnel in terms of jitter and convergence time, namely the average convergence time of Virtual Link is 24.1166 seconds while GRE Tunnel is 28.6144 seconds. Nonetheless, GRE Tunnel shows lower packet loss at large data sizes. This study provides practical guidance for network professionals in optimizing multi-area OSPF configurations.